2017
DOI: 10.1038/srep41352
|View full text |Cite
|
Sign up to set email alerts
|

Role of thermal physiology and bioenergetics on adaptation in tree shrew (Tupaia belangeri): the experiment test

Abstract: Ambient conditions, as temperature and photoperiod, play a key role in animals' physiology and behaviors. To test the hypothesis that the maximum thermal physiological and bioenergetics tolerances are induced by extreme environments in Tupaia belangeri. We integrated the acclimatized and acclimated data in several physiological, hormonal, and biochemical markers of thermogenic capacity and bioenergetics in T. belangeri. Results showed that T. belangeri increased body mass, thermogenesis capacity, protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 86 publications
(106 reference statements)
4
13
0
Order By: Relevance
“…The cage environment was maintained on a 12L:12D cycle (lights on at 08:00), 25 ± 1°C, and 65-92% relative humidity. The shrews were fed a food mixture containing 25.0% crude protein, 6.3% crude fat, 4.6% crude fiber, 7.4% ash, and 0.96 kJ/g gross energy, as well as apples, pears and other fruits twice weekly (Zhang et al 2017).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The cage environment was maintained on a 12L:12D cycle (lights on at 08:00), 25 ± 1°C, and 65-92% relative humidity. The shrews were fed a food mixture containing 25.0% crude protein, 6.3% crude fat, 4.6% crude fiber, 7.4% ash, and 0.96 kJ/g gross energy, as well as apples, pears and other fruits twice weekly (Zhang et al 2017).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The data derived from the Mx3000P quantitative software were expressed as relative amounts. Gene expression was calculated by the 2 −ΔΔCt method (Zhang et al 2017).…”
Section: Histomorphological Studymentioning
confidence: 99%
See 2 more Smart Citations
“…T. belangeri often perch in coniferous and broad-leaved forests, where they mainly eat fruit, insects and other animal food (Kawamichi, 1982). Now it is being used as a promising animal model in biomedical research, physiological and morphological characteristics were reported (Zhang et al, 2017;Gao et al, 2016;Zhang et al, 2014;Gao et al, 2014), but chemical communication in urine on kin recognition had never been known. Volatile chemical substances in urine of the kinship and non-kinship Tupaia belangeri were measured in the present study, we hypothesized that volatile chemicals in urine may related to its kin recognition in T. belangeri.…”
mentioning
confidence: 99%